Negative perception in those at highest risk--potential challenges in colorectal cancer screening in an urban asian population - Hilmi, Ida; Hartono, Juanda Leo; Goh, Khean Lee (West Asia Organization for Cancer Prevention, 2010)
Knowledge of CRC and CRC screening is low among the Malaysian population. The majority are not willing to undergo screening, the Chinese paradoxically being the least willing despite being at greatest risk.